Media and information literacy among mothers in the 21st century: A scoping review protocol - Yuan Jiang; Normah Mustaffa; Jamaluddin Aziz; XiaoChun Cai (PLoS ONE, 2025)
Background Media and information literacy (MIL) is one of the most essential competencies people need in the 21st century. Although extensive research has focused on children and students, the MIL status of mothers, who are not only huge seekers and consumers of media and information but also crucial interventionists in family MIL, remains in its infancy. Objective The objective of this scoping review is to systematically map the existing studies on mothers’ MIL in the 21st century. Specifically, it aims to perform a bibliometric analysis of relevant research; clarify the condition of mothers’ MIL in the 21st century; summarize the theoretical frameworks and measurement methodologies; and identify key influencing variables. Inclusion criteria All primary or peer-reviewed articles on mothers’ MIL published after 2000 will be included, regardless of language or region. There are no participant restrictions, such as age, region, marital status, etc. All relevant concepts, such as “computer literacy,” “digital literacy,” “Information and Communications Technology (ICT) literacy,” “information literacy,” “MIL,” “media literacy,” “news literacy,” “social media literacy,” “technology literacy,” and “visual literacy” are included. Methods The review will adhere to the JBI’s Scoping Review Guidelines and utilize the PRISMA-ScR reporting standards. A comprehensive search strategy based on the PCC framework will be applied across four databases: Web of Science, Scopus, EBSCOhost and Taylor& Francis. Two reviewers will separately search the databases in a two-round screening and extract data using a designated extraction instrument to respond to review queries. The search strategy and the instrument had been refined through a pilot test. A PRISMA flow diagram will be used to depict the entire screening procedure. Registration This scoping review protocol has been registered in the Open Science Framework (https://doi.org/10.17605/OSF.IO/2N5V7).